A best‐worst scaling experiment to identify patient‐centered claims‐based outcomes for evaluation of pediatric antipsychotic monitoring programs. (28th December 2020) - Mackie, Thomas I.; Kovacs, Katherine M.; Simmel, Cassandra; Crystal, Stephen; Neese‐Todd, Sheree; Akincigil, Ayse
Abstract: Objective: This article employs a best‐worst scaling (BWS) experiment to identify the claims‐based outcomes that matter most to patients and other relevant parties when evaluating pediatric antipsychotic monitoring programs in the United States. Data Sources: Patients and relevant parties, with pediatric antipsychotic oversight and treatment experience, completed a BWS experiment, including policymakers (n = 31), foster care alumni (n = 28), caseworkers (n = 23), prescribing clinicians (n = 32), and caregivers (n = 18). Study Design: Respondents received surveys with a scenario on antipsychotic monitoring programs and ranked 11 candidate claims‐based outcomes as most and least important for program evaluation. Data Analysis: Stratified by respondent group, best‐worst scores were calculated to identify the relative importance of the claims‐based outcomes. A conditional logit examined whether candidate outcomes for safety, quality, and unintended consequences were preferred over reduction in antipsychotic treatment, the outcome used most often to evaluate antipsychotic monitoring programs. Principal Findings: Safety indicators (eg, antipsychotic co‐pharmacy, cross‐class polypharmacy, higher than recommended doses) ranked among the top three candidate outcomes across respondent groups and were an important complement to antipsychotic treatment reduction. Foster care alumni prioritized "antipsychotic treatment reduction" and "increased psychosocial treatment." Caseworkers, prescribers, and caregivers prioritized "increased follow‐up after treatment initiation." Potential unintended consequences of an antipsychotic monitoring program ranked lowest, including increased use of other psychotropic medication classes (as a substitute), increased psychiatric hospital stays, and increased emergency room utilization. Results of the conditional logit model found only caregivers significantly preferred other indicators over antipsychotic treatment reduction, preferring improvements in follow‐up care (5.78) and psychosocial treatment (4.53) and reduction in prescriptions of higher than recommended doses (3.64). Conclusions: The BWS experiment supported rank ordering of candidate claims‐based outcomes demonstrating the opportunity for future studies to align outcomes used in antipsychotic monitoring program evaluations with community preferences, specifically by diversifying metrics to include safety and quality indicators.